THE 80TH ANNIVERSARY OF THE DEPARTMENT OF FACULTY PEDIATRICS OF N.I. PIROGOV RUSSIAN NATIONAL SCIENTIFIC MEDICAL UNIVERSITY - G.A. Samsygina; L.S. Namazova-Baranova; T.V. Kazyukova (Union of pediatricians of Russia, 2011)
(Педиатрическая фармакология. - 2011; 8 (6): 142-145).